Pembatasan Sosial Berskala Besar dalam Perpektif Hukum dan Fikih Siyasah - Mayang Yuliandari Effendi Siregar (TANFIDZIY, 2023)
Indonesia has declared the Covid-19 public health emergency as a public health emergency that must be implemented in overcoming public diseases and/or public health risk factors so that the Covid-19 outbreak and public health emergencies can be resolved immediately, one of the health quarantine measures is in the form of restrictions. This type of research is in the form of library research. The results of the research that the author gets, Large-Scale Social Restrictions in the perspective of Law and Fikih  Siyasah, namely Regarding the rules of the Large-Scale Social Restriction Program which closes schools, limits work outside the home and limits religious activities outside the home. Restrictions on religious activities, as one of the PSBB policies in limiting congregational worship activities, are certainly aimed at the public good. In Islamic Law, the Large-Scale Social Restrictions Program is considered a form of government jihad for the safety of its people during the pandemic. Government policies such as this PSBB are a manifestation of Islamic legal theory in the frame of al-dharuriyyat al-khamsah which prioritizes 3 (three) important categories, namely the preservation of religion (hifdz al-diin), the preservation of life / life (hifdz al-nafs), and the preservation of property (hifdz al-maal).